A prospective cohort study providing insights for markers of adverse pregnancy outcome in older mothers - Samantha C. Lean; Rebecca L. Jones; Stephen A. Roberts; Alexander E. P. Heazell (BMC, 2021)
Abstract Background Advanced maternal age (≥35 years) is associated with increased rates of adverse pregnancy outcome. Better understanding of underlying pathophysiological processes may improve identification of older mothers who are at greatest risk. This study aimed to investigate changes in oxidative stress and inflammation in older women and identify clinical and biochemical predictors of adverse pregnancy outcome in older women. Methods The Manchester Advanced Maternal Age Study (MAMAS) was a multicentre, observational, prospective cohort study of 528 mothers. Participants were divided into three age groups for comparison 20-30 years (n = 154), 35-39 years (n = 222) and ≥ 40 years (n = 152). Demographic and medical data were collected along with maternal blood samples at 28 and 36 weeks' gestation. Multivariable analysis was conducted to identify variables associated with adverse outcome, defined as one or more of: small for gestational age (< 10th centile), FGR (<5th centile), stillbirth, NICU admission, preterm birth < 37 weeks' gestation or Apgar score < 7 at 5 min. Biomarkers of inflammation, oxidative stress and placental dysfunction were quantified in maternal serum. Univariate and multivariable logistic regression was used to identify associations with adverse fetal outcome. Results Maternal smoking was associated with adverse outcome irrespective of maternal age (Adjusted Odds Ratio (AOR) 4.22, 95% Confidence Interval (95%CI) 1.83, 9.75), whereas multiparity reduced the odds (AOR 0.54, 95% CI 0.33, 0.89). In uncomplicated pregnancies in older women, lower circulating anti-inflammatory IL-10, IL-RA and increased antioxidant capacity (TAC) were seen. In older mothers with adverse outcome, TAC and oxidative stress markers were increased and levels of maternal circulating placental hormones (hPL, PlGF and sFlt-1) were reduced (p < 0.05). However, these biomarkers only had modest predictive accuracy, with the largest area under the receiver operator characteristic (AUROC) of 0.74 for placental growth factor followed by TAC (AUROC = 0.69). Conclusions This study identified alterations in circulating inflammatory and oxidative stress markers in older women with adverse outcome providing preliminary evidence of mechanistic links. Further, larger studies are required to determine if these markers can be developed into a predictive model of an individual older woman's risk of adverse pregnancy outcome, enabling a reduction in stillbirth rates whilst minimising unnecessary intervention.